Model Penerimaan Pengguna untuk Aplikasi Mobile Virtual Hotel Operator - Graha Prakarsa; Vani Maharani Nasution; Tombak Gapura Bhagya (Sainteks: Jurnal Sain dan Teknik, 2021)
The growth of technology allows people today to easily book hotel rooms according to their own needs and desires, this is possible thanks to the Virtual Hotel Operator (VHO) application in Indonesia. Seeing this situation, we need a model that is able to measure the extent to which the level of acceptance of the VHO mobile application. It is necessary to know the factors that indirectly influence acceptance in the use of VHO applications by combining the Technology Acceptance Model (TAM) which is used as the basic model which is the aim of this study. The quantitative approach was used in this study, while the data collection technique was using questionnaires. The data analysis technique uses linear regression. This research concludes that the compatibility and trust variables have an indirect effect on the intention to use the VHO mobile application. Keywords: TAM, Compatibility, Trust, VHO